Synthesis of an octathienyl-fused phthalocyanine as a donor material for organic solar cells. (March 2015) - Yan, Xiaoyang; Fan, Haijun; Gu, Hongfei; Zhang, Junliang; Huang, Xuebin; Zhang, Rubo; Zhan, Xiaowei
Abstract: We report the synthesis and properties of a phthalocyanine derivative with eight fused thienyl rings and eight triisopropylsilylethynyl substituents. The fused thienyl rings were designed to enhance intermolecular interactions among the phthalocyanine molecules in the solid state whereas the triisopropylsilylethynyl substituents were aimed to improve solubility. Compared to the simple octa(2-thienyl) substituted phthalocyanine, a remarkable decrease of solubility and a 67 nm red shift in UV–visible absorption maximum were observed. The fused thienyl compound was used as a donor material in bulk heterojunction solar cells. The power conversion efficiency of 0.60% was achieved under simulated solar illumination. Highlights: A phthalocyanine with eight fused thienyl rings was synthesized. The phthalocyanine showed the Q-band absorption at 774 nm. The phthalocyanine was used as a donor in bulk heterojunction solar cells. A power conversion efficiency of 0.60% was achieved in the solar cell device.